Hematological and biochemical parameters changes associated with Coronavirus Disease (COVID-19) for some patients in Missan Province - Anas, S. Abuali ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2024)
COVID-19 an infectious respiratory illness caused by the severe acute respiratory syndrome–corona virus 2 (SARS-CoV2), has now spread to multiple countries including Iraq, therefore this study aimed at the detection of the relationship of hematological and biochemical markers with SARS-CoV-2 infection in Missan city. Method: The study was performed in Period between (First of November  -2021 to  First of May- 2022), the data and blood samples were collected from 92 (55 males and 37 females) in Maternity and Baby hospital (COVID-19 center ).the patients were conformed as positive for SARS-CoV-2 nucleic acid by fluoresce RT-PCR .Each infected patient was subjected to the blood grouping test according to the procedure that described in kit of blood grouping from supplier in Chennai(India). Five (5ml) of venous blood samples were collected, Each blood sample separated into two tubes, The first sample (2ml) of the blood added to EDTA tube for hematological assessment ,the second blood sample (3ml) added to the tube without anticoagulant and centrifugation for (10 minutes) at 3000 rpm , the serum was stored in (-20C˚)freezer till handled for biochemical analysis and all biochemical parameters were performed in laboratory of Baby and Maternity hospital according to the standard methods that described in the analysis kits products in Spinach Company  Spain  react. Complete blood picture (CBC) were shown from the collected blood samples by automatic methods (System X kx-21n automated hematology analyzer; JAPAIN CARE CO., LTD).